2023
DOI: 10.3390/su15086376
|View full text |Cite
|
Sign up to set email alerts
|

How Digitalization Shapes Export Product Quality: Evidence from China

Abstract: Digitalization has imposed new production and trade requirements on enterprises. Quality upgrading of export products, a requirement of international consumption upgrading, is also a product of enterprise industrial upgrading. We examine the impact of the digitalization of Chinese listed firms on the quality of their export products from 2011 to 2015 using the panel fixed effects model and chain mediating effects model. The results demonstrate that digitalization has an inverted U-shaped effect on the quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…With technological innovation, the competitive advantage of the product itself is significantly highlighted by substantially reducing production costs [34,35]. Technological innovation enables enterprises to autonomously analyze, develop, and process products, thus independently determining product quality and aiding in its enhancement [36][37][38]. It allows for product refinement according to diverse consumer needs, increasing market recognition and brand influence, thereby elevating brand value and opening international markets to enhance global market competitiveness [39].…”
Section: Theoretical Analysis and Research Questionsmentioning
confidence: 99%
“…With technological innovation, the competitive advantage of the product itself is significantly highlighted by substantially reducing production costs [34,35]. Technological innovation enables enterprises to autonomously analyze, develop, and process products, thus independently determining product quality and aiding in its enhancement [36][37][38]. It allows for product refinement according to diverse consumer needs, increasing market recognition and brand influence, thereby elevating brand value and opening international markets to enhance global market competitiveness [39].…”
Section: Theoretical Analysis and Research Questionsmentioning
confidence: 99%
“…The digital economy has brought new opportunities and challenges to global economic and trade cooperation (Zhang & Duan, 2023), and SMEs must urgently enhance their international competitiveness in the digital economy era. This study uses a quasi-natural experiment in a comprehensive pilot zone of cross-border e-commerce at the city level in China to investigate the effects of cross-border e-commerce development on the internationalization and competitiveness of SMEs.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…This urgently requires SMEs in developing countries to seek new sources of competitive advantage rather than traditional advantages of low resource costs, while the development of digital technology and digital trade has given SMEs new opportunities for international competitive advantage (Chen & Yang, 2017; Yang et al, 2023). Previous studies have found that e-commerce and digital trade can promote enterprises’ export competitiveness, but these studies mainly focus on large enterprises (He et al, 2011; Zhang & Duan, 2023). Limited by data availability, there is relatively little research on the relationship between cross-border e-commerce and international competitiveness.…”
Section: Background and Theoretical Analysismentioning
confidence: 99%
“…, 2023), customer integration (Xi et al. , 2023), export product quality (Zhang and Duan, 2023) and enhances the business competitiveness (Kongrode et al. , 2023).…”
Section: Introductionmentioning
confidence: 99%